Naloxone Administration by Untrained Community Members. Issue 1 (17th December 2019) - Eggleston, William; Calleo, Vincent; Kim, Martin; Wojcik, Susan
Abstract : Study Objective: Access to naloxone is a priority for reducing opioid deaths. Although community members who complete naloxone training are able to administer nasal naloxone successfully and rapidly, little is known about the ability of community members to administer naloxone without training. The objective of this study was to assess the ability of untrained individuals to administer naloxone successfully in a simulated opioid overdose setting. Design: Prospective single‐site open‐label randomized usability assessment. Setting: Scenario station at a large state fair during August and September 2017. Participants: A total of 207 healthy adults who were randomly assigned to administer naloxone using a nasal spray (NS) device (69 participants), an intramuscular (IM) kit (68 participants), or an improvised nasal atomizer (AT) kit (70 participants). Intervention: Participants were instructed to administer the device to a high‐fidelity mannequin in a public environment with distractions to mimic those that might be present in an actual overdose. No device instructions or administration materials were provided. Measurements and Main Results: Participants were assessed by trained study team members who directly observed all naloxone administrations using the predetermined end‐point criteria. Individual participant perceptions were evaluated immediately following the naloxone administration using a standardized questionnaire form. The primary outcome was successful administration, defined as administration within 7 minutes and without critical errors. Secondary outcomes were time to successful naloxone administration and ease of use of the device. The NS (66.7%, p<0.001) and IM (51.5%, p<0.001) devices had higher rates of successful administration than the improvised nasal AT device (2.9%). The NS device was administered more rapidly (median 16 sec) than the IM device (median 58 sec, p<0.001) or improvised nasal AT device (median 113 sec, p=0.012) devices, and it was the easiest to use. Conclusion: In this study of naloxone administration, participants administered the NS and IM devices more successfully than the AT device. The NS device was administered most rapidly and was easiest to use.